2014
DOI: 10.1007/s40435-014-0133-2
|View full text |Cite
|
Sign up to set email alerts
|

A robust time delay auto-regressive exogenous fuzzy inference system for real-time estimation of catalyst temperature over engines coldstart operation: a multiobjective implementation scenario

Abstract: In the current investigation, the authors propose an intelligent real-time system to dynamically simulate the catalyst temperature in automotive engines over the coldstart period. In general, the behavior of an engine during the first few minutes of its operation, namely the coldstart period, is highly transient and nonlinear. However, it is important to the engineers of automotive industry to develop advanced simulation techniques capable of capturing the engine system's behavior during coldstart periods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In the rest of this section, the authors will explain how the concept of ARX system implementation can be used to prepare MVLNNs for real-time applications. ARX enables us to reform the basic structure of MVLNNs to a time-delay-based network which can be used for studying the underlying dynamics of nonlinear systems (Mozaffari and Azad, 2014b). In this context, we need to add a finite number of delays (lags) to the measured input/output signals.…”
Section: Controlling Parameters Of Mvlnn 107mentioning
confidence: 99%
See 2 more Smart Citations
“…In the rest of this section, the authors will explain how the concept of ARX system implementation can be used to prepare MVLNNs for real-time applications. ARX enables us to reform the basic structure of MVLNNs to a time-delay-based network which can be used for studying the underlying dynamics of nonlinear systems (Mozaffari and Azad, 2014b). In this context, we need to add a finite number of delays (lags) to the measured input/output signals.…”
Section: Controlling Parameters Of Mvlnn 107mentioning
confidence: 99%
“…where ε is the white noise signal measured at time t. Based on a theoretical analysis, it has been demonstrated that white noises can be modeled using a proper Gaussian function (Mozaffari and Azad, 2014b). Therefore, if experiments reveal that the realtime white noise error is significant, we can fit a Gaussian function to capture the error and further improve the performance of AMVLNN.…”
Section: Multiplevalued Logic Neuronsmentioning
confidence: 99%
See 1 more Smart Citation